THERMOGRAVIMETRIC INVESTIGATIONS OF VAGINAL SUPPOSITORY WITH THYME OIL - N. V. Melnikova; V. V. Gladishev; B. S. Burlaka (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
One of the main stages in new medicines creation is the development of their making technology. Technological process of suppository making includes ratherlongthermal treatment during preparation and homogenization of suppository base, active substancesaddition. These factors create danger of chemical and physical transformation of active substances and excipients in suppository up to their destruction and change of pharmacological and physical-chemical properties. Use of thermogravimetric analysis in pharmaceutical technology allows to studythepossibility of chemical interaction in dosage forms over the wide temperature range.